Community-acquired pneumonia: risk factors, prognosis, microbial etiology, treatment, and prophylaxis - Catia Cilloniz; Antoni Torres (Barcelona Respiratory Network Reviews)
Community-acquired pneumonia (CAP) is a significant global health problem with a considerable clinical burden. It especially affects children under 5 years old, the elderly, people with multiple comorbidities, and the immunocompromised. Despite advances in the diagnosis and treatment of CAP, mortality rates remain high, particularly among patients who develop severe pneumonia with life-threatening complications. Notably, the long-term consequences of CAP include the worsening of pre-existing comorbidities, the development of new medical conditions, and a reduction in life expectancy, especially in older adults. Key factors that influence mortality include the initial severity of disease, the presence of prior comorbidities, and the status of the immune system. This review discusses current scientific evidence and emerging data on various aspects of CAP, including changes in its epidemiology, the role of viral causes, updated treatment approaches, the use of corticosteroids, and available preventive measures.